2021
DOI: 10.1159/000511116
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Evaluation of Transurethral Resection of the Prostate versus Plasmakinetic Enucleation of the Prostate in the Treatment of Massive Benign Prostatic Hyperplasia

Abstract: <b><i>Background:</i></b> Benign prostatic hyperplasia (BPH) is a common chronic progressive disease resulting in urinary obstruction in aging men. It comes to more and more patients with massive BPH with the aging of society and extension of life expectancy. <b><i>Objective:</i></b> The aim of the study was to compare the clinical efficacy, safety, and complications between transurethral bipolar plasmakinetic enucleation of the prostate (PKEP) and transurethral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…However, some patients may suffer from postoperative bleeding due to the fragility of the fossa at the prostate to surgical interference, which compromises the curative effect [ 4 ]. Therefore, postoperative bleeding of BPH is a major clinical issue to be addressed [ 5 , 6 ]. To date, summaries and analyses of common factors of postoperative bleeding have been made by many scholars, and relevant influencing factors include defecation straining, cough, improper surgical operation, and nursing methods [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients may suffer from postoperative bleeding due to the fragility of the fossa at the prostate to surgical interference, which compromises the curative effect [ 4 ]. Therefore, postoperative bleeding of BPH is a major clinical issue to be addressed [ 5 , 6 ]. To date, summaries and analyses of common factors of postoperative bleeding have been made by many scholars, and relevant influencing factors include defecation straining, cough, improper surgical operation, and nursing methods [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For another, intraoperative bleeding has always been a serious problem in surgery process [ 21 ]. Nevertheless, many previous studies used a simple formula to estimate intraoperative blood loss volume [ 6 , 11 , 22 , 23 ], which might not accurately reflect the real blood loss volume. To better evaluate the blood loss and fluid absorption, the endoscopic surgical monitoring system was developed and used in BPH surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that the study by Ran et al that suggested no difference between PK-EEP and PK-TURP in terms of fluid absorption [ 17 ] failed to stratify the patients based on their prostate volume. The benefits of applying PK-EEP in patients with relatively large prostate volume might be due to the fact that the hyperplastic prostate tissue was peeled off directly along the surgical capsule which could remove more tissue and avoided excessive opening venous sinus in prostate [ 6 ]. So, in our data, for prostate volume > 40 ml with PK-EEP, more tissues were removed, and the blood loss and fluid absorption volume through the intravascular pathway were decreased, therefore reduced the postoperative bladder irrigation and catheterization indwelling period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 The common complications after prostate surgery due to indwelling catheter and bladder drainage include bladder spasm (BS) and catheter-related bladder discomfort (CRBD). 3 , 4 12.9–28.3% 5 of patients experience BS. Some patients experience both BS and CRBD.…”
Section: Introductionmentioning
confidence: 99%